2015
DOI: 10.1152/ajplung.00259.2014
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic M3receptors on structural cells regulate cigarette smoke-induced neutrophilic airway inflammation in mice

Abstract: Anticholinergics, blocking the muscarinic M3 receptor, are effective bronchodilators for patients with chronic obstructive pulmonary disease. Recent evidence from M(3) receptor-deficient mice (M(3)R(-/-)) indicates that M3 receptors also regulate neutrophilic inflammation in response to cigarette smoke (CS). M(3) receptors are present on almost all cell types, and in this study we investigated the relative contribution of M(3) receptors on structural cells vs. inflammatory cells to CS-induced inflammation usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Interestingly, wildtype animals receiving M 3 R -/-bone marrow cells showed a similar increase in neutrophil number, suggesting that the M 3 receptor on inflammatory cells is not involved in the pro-inflammatory effect of acetylcholine. By contrast, no increase in the number of neutrophils was observed in M 3 R -/-animals receiving wildtype bone marrow cells, suggesting a critical role for airway structural cells in the pro-inflammatory effect of acetylcholine [28].…”
Section: Copdmentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, wildtype animals receiving M 3 R -/-bone marrow cells showed a similar increase in neutrophil number, suggesting that the M 3 receptor on inflammatory cells is not involved in the pro-inflammatory effect of acetylcholine. By contrast, no increase in the number of neutrophils was observed in M 3 R -/-animals receiving wildtype bone marrow cells, suggesting a critical role for airway structural cells in the pro-inflammatory effect of acetylcholine [28].…”
Section: Copdmentioning
confidence: 77%
“…As is evident from the various in vitro studies described above, both structural cells and inflammatory cells can contribute to the pro-inflammatory effects of acetylcholine, and it is not known whether this effect is primarily mediated via M 3 receptors on structural cells or via M 3 receptors on inflammatory cells. Recently, using bone marrow chimeric animals, it was shown that this is primarily mediated via M 3 receptors on structural cells [28]. Exposure to cigarette smoke induced neutrophilic inflammation in non-irradiated and irradiated control animals.…”
Section: Copdmentioning
confidence: 99%
“…Evidence from M3 muscarinic receptor-deficient mice indicates that this receptor regulates neutrophilic inflammation in response to cigarette smoke. In murine models of asthma, antagonism of M3 alleviates airway hyperresponsiveness, neutrophil-mediated inflammation, and airway remodeling (49). As mentioned above, M3 receptor signaling may also play a causal role in specific idiopathic autoimmune diseases.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, cough frequency was independently associated with being a current smoker, smoking history, sputum production and neutrophilic inflammation 39. A recent study has demonstrated that M3 receptors may play a proinflammatory role in cigarette smoke-induced inflammation in animal models of COPD, suggesting another potential mechanism by which LAMAs may improve cough in patients with COPD 44. This is further supported by preclinical studies that have shown LAMAs can reduce neutrophils and inflammatory mediators, such as interleukin-6, tumour necrosis factor-α and interferon-γ, in cigarette smoke-exposed animal models 45…”
Section: Discussionmentioning
confidence: 99%